Extraordinarily Large Malignant Extra Gastro Intestinal Stromal Tumor Presenting as an Abdominal Mass - Paudyal, P; Subba, TN; Pradhan, A; Dhakal, S; Karki, S; Paudyal, P (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Gastrointestinal stromal tumors (GIST) are rare of all gastrointestinal neoplasms with histology and immunohistochemistry similar to gastrointestinal stromal tumors. They occur outside the gastrointestinal tract rarely and are, hence, called the extra gastrointestinal stromal tumors (EGIST). Herein, we report a rare case of malignant extra intestinal gastrointestinal tumor. Case report: A 39 yr old female presented to the surgical OPD with a lump in the abdomen since 4 months. We received a lobulated tumor which measured 40x25x20 cm3 and showed capsule. Cut surface was predominantly solid, grey white with areas of hemorrhage and necrosis along with cystic areas. Histopathology and immunohisto chemistry revealed it to be a malignant EGIST of mesentery because of no continuity of the tumor with the small intestine microscopically. Conclusion: EGIST is a rare no epithelial tumor of mesentery. Omentum histopathological examination is a standard technique to diagnose the tumor and to differentiate it immunohistochemically from other tumors having similar morphology. Correct diagnosis plays valuable role in the treatment.